2016
DOI: 10.1007/s10661-016-5245-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of land use change on ecosystem services in China

Abstract: Land use change can greatly alter spatial pattern and overall ecosystem service values (ESV). The goal of this study was to explore the likely effects of land use change on ESV in China. In this paper, the spatially explicit land use changes across China from 2010 to 2020 under the 2000s trend scenario and the planning scenario were projected using the Dyna-CLUE model. The ESV evaluation method was improved by adjusting the ESV coefficients using biomass data to reduce the generalization error of proxy-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The "reform and opening up policy", implemented in China in 1978, generated impressive expansion of cultivated lands, significantly altering the land structure [49]. Along with the "China market economy policy" enacted in 1992, tremendous LULCC occurred in the study area, especially where natural resources were available for the expansion of cultivated lands [50].…”
Section: The Influence Of Policymentioning
confidence: 99%
“…The "reform and opening up policy", implemented in China in 1978, generated impressive expansion of cultivated lands, significantly altering the land structure [49]. Along with the "China market economy policy" enacted in 1992, tremendous LULCC occurred in the study area, especially where natural resources were available for the expansion of cultivated lands [50].…”
Section: The Influence Of Policymentioning
confidence: 99%
“…Identifying the factors that influence ES is a key step in understanding the spatial scale dependence of ES relationships and essential to managing multiple ES to improve ecosystem functions 31 , 32 . Nevertheless, the drivers of ES supply are complex, and the mechanisms underlying ES relationships are not straightforward 6 , 12 , 33 . Biophysical and socio-economic factors can be considered the main types of drivers that affect the spatial heterogeneity of ES 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been performed to monitor the impact of LULC changes on the structure and functions of ESV in numerous regions of China [4,10,18,[23][24][25][26][27][28][29][30][31][32][33] and around the world [15,25,28,29,[34][35][36][37][38][39][40][41][42][43][44][45]. Due to LULC changes and urbanization, most of these studies showed moderate to significant decrease in ESV [15,16,28,29,41,43] while others found almost no change [46].…”
mentioning
confidence: 99%